2019
DOI: 10.1007/s40258-019-00499-y
|View full text |Cite|
|
Sign up to set email alerts
|

Health Insurance in Sub-Saharan Africa: A Scoping Review of the Methods Used to Evaluate its Impact

Abstract: We conducted a scoping review with the objective of synthesizing available literature and mapping what designs and methods have been used to evaluate health insurance reforms in sub-Saharan Africa. We systematically searched for scientific and grey literature in English and French published between 1980 and 2017 using a combination of three key concepts: "Insurance" and "Impact evaluation" and "sub-Saharan Africa". The search led to the inclusion of 66 articles with half of the studies pertaining to the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The existing body of literature on health insurance and universal health coverage (UHC)42 47 48 guided the selection of independent variables included in the analyses, which were grouped into two broad categories: individual-level and household/community-level variables. Individual-level variables included current women’s age (in years), education (in years completed), marital status, religion, working status, index of media exposure, parity, antenatal care attendance and husband/partner’s education.…”
Section: Methodsmentioning
confidence: 99%
“…The existing body of literature on health insurance and universal health coverage (UHC)42 47 48 guided the selection of independent variables included in the analyses, which were grouped into two broad categories: individual-level and household/community-level variables. Individual-level variables included current women’s age (in years), education (in years completed), marital status, religion, working status, index of media exposure, parity, antenatal care attendance and husband/partner’s education.…”
Section: Methodsmentioning
confidence: 99%
“…7 8 A large number of studies examined the effects of health insurance-mainly voluntary CBHI schemes or national health insurance-on health service utilisation and health-related financial protection. [9][10][11][12][13] Thus, health insurance has generally been found to improve access to healthcare in LMICs. In parallel, studies reported mixed results as to whether health insurance provides healthrelated financial protection.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…They highlight inter alia the need for transparent mechanisms to establish payment rates and for a sound legal framework to ensure that payment arrangements assist public purchasers to strategically purchase private healthcare under the public system. Degroote et al [ 30 ] conduct a scoping review of the methods used to evaluate the impact of health insurance. They observe that the evidence for the impact of health insurance in SSA is derived primarily from observational studies that cannot discern causal relationships but only highlight an association between the outcome of interest and insurance exposure.…”
Section: Content Of This Special Issuementioning
confidence: 99%